Avaliação da eficiência de recuperação de um líquido contido em um meio poroso por injeção de líquidos Newtonianos e não-newtonianos - Souza, Alexandre Willig Quintino de (2018)
The application of tertiary recovery methods to increase the recovery factor of oil fields,especially in heavy oil reservoirs, has increased considerably due to the efficiency ofprimary and secondary oil recovery methods do not be more than 30%. Among thesemethods, the injection of chemicals can be cited. To apply these methods, it is impor-tant to understand the phenomenology of liquid-liquid displacement occurring within aporous medium. In this work, the influence of the viscosity ratio and the non-Newtonianproperties, particularly viscoplasticity and viscoelasticity, on the recovered mass of aliquid initially contained in a porous medium was analysed. Using an experimentalapproach, different Newtonian solutions, a viscoplastic solution and a viscoelastic so-lution were used to displace a Newtonian liquid that fills the pores. In this work, it wasshown for the Newtonian case that the lower the viscosity ratio, the greater the dis-placed liquid fraction recovered. In the viscoplastic case, the lost mass fraction wasgreater than the equivalent Newtonian case due to a chemical reaction between thefluids. On the other hand, in the viscoelastic scenario, depending on the concentrationof PEO used, the recovery efficiency was identical or greater than the correspondingNewtonian scenario.